2003
DOI: 10.1159/000067033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Omentectomy on Peritoneal Defense Mechanisms in an Experimental Model of Intra-Abdominal Infection

Abstract: Background/Aim: The omentum has an important role as part of peritoneal defense mechanisms. The aim of this study is to show the bactericidal activity of peritoneal fluid and the role of the omentum as a peritoneal defense mechanism in experimental animals with intra-abdominal infections. Methods: 40 male Spraque-Dawley rats weighing between 250 and 300 g were used in this study. The rats were randomly divided into four groups consisting of 10 animals. The operative procedures were done under sterile condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
(11 reference statements)
0
10
0
2
Order By: Relevance
“…Several studies have shown no survival difference between partial and complete omentectomy as part of radical gastrectomy for gastric cancer. A retrospective study in 196 patients found no difference in 3‐ and 5‐year relapse‐free survival in patients in whom omentectomy was performed as part of radical gastrectomy compared with those in whom omentum‐preserving gastrectomy was undertaken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown no survival difference between partial and complete omentectomy as part of radical gastrectomy for gastric cancer. A retrospective study in 196 patients found no difference in 3‐ and 5‐year relapse‐free survival in patients in whom omentectomy was performed as part of radical gastrectomy compared with those in whom omentum‐preserving gastrectomy was undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…The greater omentum is the primary peritoneal defence organ responsible for the clearance of bacteria from the peritoneal cavity. The greater omentum reduces intestinal adhesions, not only by interposing between the abdominal viscera and the abdominal wall to create a mechanical barrier, but also because its mesenchymal cells produce fibrinolytic factors. Notably, high‐quality evidence for a survival benefit of complete omentectomy is lacking; retrospective studies have shown no difference between omentectomy compared with omentum‐preserving strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the peritoneal bacterial activity against Escherichia coli does not change after omentectomy. Finally, in a case report of an obese patient with multiple rib fractures and increased abdominal pressure, omentectomy allowed to perform successful weaning from mechanical ventilation [15]. With all these eventual beneficial aspects of omentectomy in morbidly obese patients, the question is: why is this not a routine surgical step when performing any type of bariatric surgery?…”
Section: Discussionmentioning
confidence: 99%
“…73 In rodent models, however, omentectomy does not decrease the bactericidal activity of peritoneal fluid, 74 nor does it increase bacterial counts in a model of cecal perforation. 75 The same group looked at the effect of omentectomy on the inflammatory phase of anastomotic healing and found that there was no difference between rats subjected to omentectomy. 76 In fact, they showed that following omentectomy, systemic compensatory mechanisms lead to the recruitment of peripheral leukocytes which mediate the healing process.…”
Section: Does Omentectomy Impair Peritoneal Defenses?mentioning
confidence: 99%